An Examination of Federal Tribal Broadband Funding Post-COVID - John, EJ (The journal of community informatics, 2026)
This article examines federal investment in Tribal broadband deployment, from the COVID-19 era to the present day. It discusses how legislation initially enacted in response to the pandemic established programs to improve digital access and connectivity in Tribal communities. While these programs did not solve every problem, they enabled Tribes to have greater control over resources to achieve the goal of expanded broadband connectivity. This reassignment of control recognized Tribal sovereignty in ways that earlier initiatives had not, and many Tribes embraced the challenges. Future funding programs must continue to empower Tribes and not mandate how Tribes use their resources. Empowering Tribal Nations to make their own decisions and providing the tools to accomplish that is a foundational part of the federal government’s trust responsibility to federally recognized Tribal Nations.